Digital Agility as a Strategic Force to Enhance Organizational Positioning - Ahmed Salah Jassam (Indonesian Journal of Law and Economics Review, 2026)
General Background: Rapid advances in information technology and digital transformation have reshaped how organizations operate and compete, particularly with the expansion of big data and cloud computing. Specific Background: Organizations are increasingly required to adopt digital approaches that differ from traditional methods to maintain and strengthen their market standing and operational processes. Knowledge Gap: Despite growing interest in digital transformation, limited clarity remains regarding how digital agility contributes to organizational positioning across institutional contexts. Aims: This study aims to examine the role of digital agility in strengthening organizational positioning and to assess the feasibility of adopting digital transformation for organizational performance. Results: Findings indicate that digital agility enables faster task completion, improves organizational efficiency, and facilitates rapid problem identification, thereby supporting stronger institutional positioning. Novelty: This study highlights digital agility as a strategic force linking operational responsiveness with institutional positioning within both corporate and academic environments. Implications: The findings suggest that organizations adopting digital agility and transformation approaches can better navigate technological change while maintaining competitive positioning and operational coherence. Highlights:• Demonstrates accelerated task processes and operational responsiveness through digital practices• Identifies organizational efficiency and rapid issue detection as key outcomes• Shows alignment between digital transformation adoption and institutional positioning Keywords: Digital Agility, Digital Transformation, Organizational Positioning, Digital Innovation, Strategic Management